Effects of Dynamic Characteristics on 5-storey Steel Tower with Different Orientation of Bracing Members - YEW, JIN QIAN; KAMARUDIN, AHMAD FAHMY (Recent Trends in Civil Engineering and Built Environment, 2022)
This paper was determined the effects of dynamic characteristics on the 5-storey steel tower with different orientation of bracing members by using the modal analysis through STAAD Pro software. There are two types of bracing systems used in the structure which is chevron bracing systems and single diagonal bracing systems. The dynamic characteristics of the 5-storey steel tower were investigated in terms of peak frequency, mode shape, maximum deflection amplitude and relative floor displacement amplitude. This study was focused on verified the comparison of the modal analysis result of the bare frame and the previous laboratory testing result. Three modes of peak frequency were produced from the modal analysis. The first three modes of result for the bare frame is 5.55Hz, 5.55Hz and 7.23Hz with the percentage difference less than 6% from the previous laboratory testing. Besides, there are different type of mode shape for chevron bracing frames and single diagonal bracing frames. The relationship of peak frequency, mode shape, maximum deflection amplitude and relative floor displacement were developed between the dynamic characteristics of the steel tower. The result of the chevron bracing systems and single diagonal bracing systems have the improvement in term of dynamic characteristic of the 5-storey steel tower. The result of chevron bracing systems has more regularity repeat and similarity of curve pattern with the bare frame.